Atividade antifúngica de óleos essenciais e produtos comerciais no controle da Mancha de alternaria em mamão - Medeiros, Isabel Cabral de (Universidade Federal Rural do Semi-Árido, 2020)
The objective of this work was to evaluate the antifungal activity of essential oils (citronella and mint) and commercial products (Tecto®, Compost Aid®, Nem Out®, Soil Set®, Enzimatic II and Serenade®) to Alternaria sp. in papaya. In the in vitro experiment, the treatments were: citronella essential oil (0.25; 0.5; 0.75; 1.0 and 1.5%), mint (0.25; 0.5; 0.75 and 1%), and commercial products Tecto® (4 mL L-1), Compost Aid® (0.5; 1.0; 1.5; 2.0 and 2.5 g L-1), Nem Out® ( 0.5; 1.0; 1.5; 2.0 and 2.5 g L-1), Soil Set® (0.5; 1.0; 2.0; 4.0 and 8 mL L-1), Enzimatic II (product under test) (0.5; 1.0; 2.0; 4.0 and 8 mL L-1) and the combinations: citronella oil (1%) + Enzimatic II (8 mL L-1), citronella oil (1%) + Enzimatic II (16 mL L-1), citronella oil (1.5%) + Enzimatic II (8 mL L-1) and citronella oil (1% ) + Enzimatic II (16 mL L-1) on the growth of Alternaria sp. In this experiment, the treatments were incorporated into the potato dextrose agar culture medium and poured into Petri dishes where a 5 mm diameter disc containing fungus structures with 12 days of cultivation was repeated. The plates were kept in an incubator with biological oxygen demand for 21 days. In the in vivo test papaya of the Formosa variety was used and the treatments were: Tecto® (4 mL L-1), Tween 20 (1%), Tween 20 (1.5%), citronella oil (1%), citronella oil (1.5%), Enzimatic II (8 ml L-1), Enzimatic II (16 ml L-1) and the combinations: citronella oil (1%) + Enzimatic II (8 ml L-1), citronella oil (1%) + Enzimatic II (16 ml L-1), citronella oil (1.5%) + Enzimatic II (8 ml L-1), citronella oil (1%) + Enzimatic II (16 mL L-1) and Serenade® (10 mL L-1). The fruits were disinfected and subsequently inoculated at three points equidistant with discs of 5 mm in diameter containing structures of the pathogen. The fruits were kept at rest for 30 minutes and then sprayed with the treatments and kept in a cold chamber at 10 ºC for 21 days. In the in vitro experiment it was found that the treatments citronella oil (1%) + Enzimatic II (8 mL L-1); citronella oil (1%) + Enzimatic II (16 mL L-1); citronella oil (1.5%) + Enzimatic II (8 mL L-1) and citronella oil (1%) + Enzimatic II (16 mL L-1) inhibited 100% the growth of Alternaria sp. The citronella oil treatments (1%); citronella oil (1.5%) and Enzimatic II (0.5 mL L-1) inhibited 47.21; 67.11 and 65.84% of the growth of the pathogen, respectively, and did not differ statistically from treatments that completely inhibited the fungus. In the in vivo experiment, the treatments Tween 20 (1.5%) and Serenade® (10 mL L-1) were better than the other treatments, however they did not differ statistically from the control, although they provided, numerically, less mycelial growth. The combinations of citronella oil and the product Enzimatic II managed to inhibit 100% of the mycelial growth of the pathogen in the in vitro experiment, however they were unable to control the development of the fungus in the in vivo experiment. Only the treatments Tween 20 (1.5%) and Serenade® (10 mL L-1) managed to reduce 17.19 and 18.94%, respectively, of the mycelial growth of Alternaria sp. in vivo, therefore, it is still necessary to carry out new work, with new treatments or changes in dosages for the evaluation of the control of the alternaria spot on papaya.
Monografia
Keywords: Carica papaya; Alternariose; Controle alternativo; Carica papaya; Alternariose; Alternative control; CIENCIAS BIOLOGICAS::BIOTECNOLOGIA